ศักยภาพของสถานีวิทยุกระจายเสียงท้องถิ่น ในจังหวัดกาฬสินธุ์กับบทบาทด้านการพัฒนาคนและสังคม - อังคณา พรมรักษา (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this research is to study popular participation in local radio in Kalasin province 1 to analyze the form and content of communication and its contribution to social development. Local factors affecting the potential of local radio in Kalasin will be studied as well. Results show that three local radio stations in Kalasin province distribute information that differs little from the content offered in metropolitan Bangkok. The national Broadcasting Service of Thailand in Kalasin provides content accounting for 47% of all programming, local content is 52% of the total. The Thai Army Second Region Radio Station in Kalasin in contrast broadcasts national programme 33.72% of the time and local 66.28% of the time. The Mass Communication Organization of Thailand in Kalasin national programme 26% of all programming and local programme 73% of all programming. Besides, the programme of daily news, documentary, music and advertisements of the three stations refects national level content rather than local content. Pattern and content focused on the local level is largely restricted to local news services and public relations. In principle, the policy of each of the three radio stations is to be local in practice more of the organization is distribute power to local management as stipulated by law.